The diagnostic value of two antigenic domains derived from the Trypanosoma cruzi Tc323 protein in chronic Chagas disease: a study in Brazil - Ossowski, Micaela S.; Silva, Ângelo Antônio Oliveira; Santos, Emily Ferreira; Leony, Leonardo Maia; Santos, Fred Luciano Neves; Gómez, Karina A. (Frontiers in Microbiology, 2025)
The diagnosis of chronic infection with the parasite Trypanosoma cruzi relies on detecting specific IgG antibodies using two or three (in the case of discordance) serological assays based on different principles. This diagnostic algorithm poses challenges in identifying patients with chronic Chagas disease (CCD), particularly in endemic areas where financial and human resources are scarce. The discovery of new antigens capable of achieving 100% sensitivity and specificity is a priority in this field. Previously, we introduced two recombinant domains, designated as rTcD3 and rTcD6 derived from a hypothetical protein from T. cruzi, as potential candidates for the diagnosis of CCD. In the current study, we extended our results by assessing the diagnostic accuracy of rTcD3 and rTcD6 in a large cohort of infected and non-infected individuals from various regions of Brazil. Both antigens showed a specificity of 97.9%, while sensitivity was 79.5% for rTcD3 and 81.5% for rTcD6. In addition, cross-reactivity analysis on 764 samples from individuals with other parasitic, bacterial and viral infections was estimated to be less than 0.9%. Specifically, one (for rTcD3) and two (for rTcD6) samples positive for leptospirosis reacted with both antigens, while 2 out of 764 samples from individuals infected with Leishmania spp., resulted in a false positive for rTcD3, while four samples behaved similarly for rTcD6. Furthermore, a false-positive reaction was also observed in one HIV-positive sample rTcD6. In conclusion, this study provides further evidence supporting the diagnostic potential of a specific and sensitive IgG-ELISA based on rTcD3 and rTcD6 for detecting chronic T. cruzi infection across various regions of the Americas, with minimal cross-reactivity with other pathogens.